Endogenous Product Differentiation, Market Size and Prices - Shon Ferguson (Research Institute of Industrial Economics (IFN), 2011)
Recent empirical evidence suggests that prices for some goods and services are higher in larger markets. This paper provides a demand-side explanation for this phenomenon when firms can choose how much to differentiate their products in a model of monopolistic competition with horizontal product differentiation. The model proposes that consumers love of variety makes them more sensitive to product differentiation efforts by firms, which leads to higher prices in larger markets. At the same time, endogenous product differentiation modeled in this way can lead to a positive and concave relationship between market size and entry.
Keywords: D43; F12; L13; 330; Endogenous Technology; Entry; Market Size Effect; International Trade; Monopolistic Competition; Produktdifferenzierung; Marktgebiet; Monopolistischer Wettbewerb; Wohlfahrtsanalyse; Transportkosten; Theorie